2004
DOI: 10.1136/jim-52-08-23
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule 1 (ICAM-1) Gene Variant Is Associated with Coronary Artery Calcification Independent of Soluble ICAM-1 Levels

Abstract: In a study sample specifically selected for the characteristic of a family history of premature coronary heart disease, ICAM K469E GG was associated with lower CAC scores in men but not women even after controlling for plasma levels of sICAM-1. These studies suggest that ICAM-1 variants may modulate atherosclerosis in humans and provide support for the concept that inflammatory gene polymorphisms may influence atherosclerosis independent of plasma levels of their gene products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The association of sICAM-1 and CAC did not remain significant in fully-adjusted models of four studies 1417 . However, these studies were limited by small sample sizes 14,17 , and low sICAM-1 assay precision 16 Tang et al 15 studied 2246 white family members in the NHLBI Family Heart Study, mean age 55 years. Unadjusted or minimally adjusted associations of sICAM-1 with CAC are concordant with our findings, but we could not identify obvious differences between our study and these other studies that would explain why sICAM-1 remained significant after full adjustment in our study.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The association of sICAM-1 and CAC did not remain significant in fully-adjusted models of four studies 1417 . However, these studies were limited by small sample sizes 14,17 , and low sICAM-1 assay precision 16 Tang et al 15 studied 2246 white family members in the NHLBI Family Heart Study, mean age 55 years. Unadjusted or minimally adjusted associations of sICAM-1 with CAC are concordant with our findings, but we could not identify obvious differences between our study and these other studies that would explain why sICAM-1 remained significant after full adjustment in our study.…”
Section: Discussionmentioning
confidence: 79%
“…If a threshold model were correct, another factor that induced exceptionally high sICAM-1 could be important. For example, genetic state could be important, since several SNP variants in the ICAM gene have been associated with elevated sICAM-1 concentration 14, 3234 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have found an association with ICAM1 SNPs and cardiovascular disease, albeit inconsistently. In a German case control study, rs5498 was associated with an OR = 2.2 for coronary heart disease 24 , in the Study of Inherited Risk of Coronary Atherosclerosis (SIRCA) this SNP was associated with CAC in men independently of sICAM-1 level 25 , and was associated with a higher risk of restenosis after coronary stenting in Chinese 26 . The rs5498 SNP was also associated with peripheral arterial occlusive disease in an Italian population 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Genome-wide association analysis indicated that ICAM-1 K469E polymorphism had a role in the genetic regulation of sICAM-1 levels [ 29 ]. In addition, Reilly et al found that ICAM-1 K469E EE genotype was associated with lower coronary artery calcification (CAC) scores in men [ 30 ]. Taken together, these data indicate that ICAM-1 K469E polymorphism can influence the risk of CAD.…”
Section: Discussionmentioning
confidence: 99%